(untitled) (Bioresearch Communications, 2025)
Background: University students experience a lot of stress due to personal, academic, financial, and other issues. Group-based stress management training can help students manage their stress effectively. Therefore, the researchers attempted to develop a stress management training manual for trainers to use with students in group training settings. Objective: The aim of this study is to develop a brief cognitive behavior therapy (CBT)-based stress management training manual for use in group settings with university students. Methodology: A mixed-methods design was followed. Initially, groundwork was conducted to understand the concept of stress through needs assessment, literature review, and expert interviews. Based on the findings, a primary draft of the manual was developed and evaluated by 12 experts. After compiling their feedback, the supervisor and researcher developed a second draft. A pilot study was then conducted, applying this manual to a group of 12 university students aged 18 to 26 years. In the pilot study, one session was held weekly for four weeks. Pre- and post-test evaluations were conducted using the Perceived Stress Questionnaire, Anxiety Scale, Depression Scale, and Dhaka University Cognitive Distortion Scale. Finally, the stress management training manual was finalized by incorporating all the findings. Findings: The manual consists of four sessions, each lasting two hours. The first session covers the concept and model of stress. The second session presents a conceptual model of stress development and introduces stress management techniques. The third session focuses on practicing cognitive distortion identification and cognitive restructuring techniques. The final session is also a practice session and covers time management and problem-solving techniques. Conclusion: This manual is a brief CBT-based training resource that can be used as a primary or secondary prevention program for stress management among university students. Bioresearch Commu. 11(2): 1811-1820, 2025 (July)